Analysis of Work Posture with Revised NIOSH Lifting Equation (RNLE) and Mental Workload with Subjective Scale of Mental Workload (ESCAM) in Employees (CV Gajah Printing) - Asyari, Hasyim; Al Hakim, Reza Azizul Nasa; Musmuallim, M.; Vargas S, Rillke Rifyal (Jurnal Ilmiah Teknik Industri, 2024)
Human resources are one of the main elements that need to be considered because of their limited abilities. The limited ability of humans to perform various kinds of physical and non-physical activities is usually influenced by work postures that are less ergonomic and excessive workload. The purpose of this study is to identify the risk of skeletal muscle injury of shopping bag plastic manufacturing operators using NIOSH Lifting, measure the mental workload of shopping bag plastic manufacturing operators using the ESCAM method, and provide suggestions for improvement using the NIOSH Lifting and ESCAM methods. Based on the results of measuring workers’ work posture with the RWL and LI equations, it is known that manual handling activities at the printing, blowing, and mixing machine workstations have an LI> 3 value, where these activities have a risk level for skeletal muscle injury. While the results of measuring employee mental workload, 2 factors can affect employee performance, namely the consequences for health and task characteristics.